Perancangan Model Proses Bisnis dan Standar Operasional Prosedur Pada PT XYZ Bagian Operations Department - Ratmananda, Diasta; Wiranti, Yuyun Tri; Insanittaqwa, Vika Fitratunnany (Equiva Journal, 2024)
Indonesia is a country rich in minerals such as gold, silver, copper, oil and natural gas, coal and others. Mining materials require a mining process which is an activity in the context of research, management, and so on. PT. Coates Hire Indonesia, which is a stakeholder in heavy equipment leasing, does not yet have a clear and documented business process and Standard Operational Procedure (SOP), especially in the Operations Department, and only has a Safe Work Procedure (SWP) and is only based on verbal instructions from the department. operation. In addition, there was a change in staff which caused the manager to have to explain the flow of activities repeatedly. Therefore, this research was conducted to model and document business processes with BPM Life Cycle using the bizagi modeler and developing SOPs using flowcharts and descriptions. The research begins with the stages of identification, discovery, after that verification of business processes and preparation of SOPs is carried out, which are then carried out by verifying SOPs. Business process modeling starts from the identification stage with interviews to find out ongoing activities and 29 activities are obtained which are modeled. Of the 29 business processes that have been verified by the process owner, an SOP document has been prepared in the form of an SOP document that has been verified and submitted by the operations department manager, and will be used as a reference for operational activities to make it more structured, effective and efficient.